Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài
Linh Phương

Tìm x:
2x(x-4)-x(2x+3)+22=0
(2x+3)(3x+2)+2(1-3x)(x+1/2)= 1

Nguyễn Việt Hoàng
18 tháng 8 2020 lúc 16:19

+) \(2x\left(x-4\right)-x\left(2x+3\right)+22=0\)

\(\Leftrightarrow2x^2-8x-2x^2-3x+22=0\)

\(\Leftrightarrow-11x+22=0\)

\(\Leftrightarrow-11\left(x-2\right)=0\)

\(\Leftrightarrow x-2=0\Leftrightarrow x=2\)

+) \(\left(2x+3\right)\left(3x+2\right)+2\left(1-3x\right)\left(x+\frac{1}{2}\right)=1\)

\(\Leftrightarrow6x^2+4x+9x+6+\left(2-6x\right)\left(x+\frac{1}{2}\right)=1\)

\(\Leftrightarrow6x^2+13x+6+2x+1-6x^2-3x=1\)

\(\Leftrightarrow12x+7=1\)

\(\Leftrightarrow x=\frac{-1}{2}\)

Khách vãng lai đã xóa
l҉o҉n҉g҉ d҉z҉
18 tháng 8 2020 lúc 19:30

2x( x - 4 ) - x( 2x + 3 ) + 22 = 0

<=> 2x2 - 8x - 2x2 - 3x + 22 = 0

<=> -11x + 22 = 0

<=> -11x = -22

<=> x = 2

( 2x + 3 )( 3x + 2 ) + 2( 1 - 3x )( x + 1/2 ) = 1

<=> 6x2 + 13x + 6 + 2( -3x2 - 1/2x + 1/2 ) = 1

<=> 6x2 + 13x + 6 - 6x2 - x + 1 = 1

<=> 12x + 7 = 1 

<=> 12x = -6

<=> x = -6/12 = -1/2

Khách vãng lai đã xóa
ミ★Ƙαї★彡
18 tháng 8 2020 lúc 19:35

\(2x\left(x-4\right)-x\left(2x+3\right)+22=0\)

\(\Leftrightarrow2x^2-8x-2x^2-3x+22=0\)

\(\Leftrightarrow-11x+22=0\Leftrightarrow x=2\)

\(\left(2x+3\right)\left(3x+2\right)+2\left(1-3x\right)\left(x+\frac{1}{2}\right)=1\)

\(\Leftrightarrow6x^2+13x+6+2x+1-6x^2-3x=1\)

\(\Leftrightarrow12x+7=1\Leftrightarrow x=-\frac{1}{2}\)

Khách vãng lai đã xóa

Các câu hỏi tương tự
Trần Hải Linh
Xem chi tiết
Gaming GF
Xem chi tiết
Do vu tuan anh
Xem chi tiết
AlexGamingVN
Xem chi tiết
Katherine Lilly Filbert
Xem chi tiết
Ta Uyen Chi
Xem chi tiết
Tạ Thị Thùy Trang
Xem chi tiết
Trần Ngọc Hà
Xem chi tiết
Trần Hoàng Nam
Xem chi tiết